Effects of Statin Therapy on Glycemic Control and Associated Factors Among Type 2 Diabetes Mellitus Patients in Northeastern Tanzania: A Retrospective Cohort Study - Daniel P. Mujuni; Kajiru G. Kilonzo; Abid M. Sadiq; Norman J. Kyala; Philip C. Makupa; Sweetness N. Laizer; Elifuraha W. Mkwizu; Furaha S. Lyamuya; Elichilia R. Shao; Erick A. Mboya; Nyasatu G. Chamba (Journal of Diabetes Research)
Conclusion: Statin therapy among patients with T2DM was associated with short-lived worsening of glycemic control at 1–3 months posttherapy.